Reanalysis of the anthrax epidemic in Rhodesia, 1978–1984 - Wilson, James M. (PeerJ, 2016)
In the mid-1980s, the largest epidemic of anthrax of the last 200 years was documented in a little known series of studies by Davies in The Central African Journal of Medicine. This epidemic involved thousands of cattle and 10,738 human cases with 200 fatalities in Rhodesia during the Counterinsurgency. Grossly unusual epidemiological features were noted that, to this day, have not been definitively explained. This study performed a historical reanalysis of the data to reveal an estimated geographic involvement of 245,750 km(2), with 171,990 cattle and 17,199 human cases. Here we present the first documented geotemporal visualization of the human anthrax epidemic.